Human Resource Management Practices on Employee Commitment: Indonesia Islamic Banking - Noor, Juliansyah; Soleh, Soleh; Faittaahumi, Meita (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract.This article discusses organizational commitment in the context of Islamic banking. Specifically, we explored whether organizational commitment relates to its human resource management practices. In addition, it will also examine the role of perceived organizational support in this relationship. To achieve this goal, we conducted an online survey at one of the branches of the largest Islamic bank in Indonesia. Data were analyzed using structural equation modeling-partial least squares (SEM-PLS). The results showed that there were problems with human resources management (HRM) practices, perceived organizational support, and organizational commitment from Islamic banks, resulting in high turnover potential. Specifically, HRM practices and perceived organizational support were positively and significantly related to organizational commitment. However, perceived organizational support only mediated the relationship between HRM practices and normative and affective commitment, but not for the relationship between HRM practices and continuance commitment.Abstrak. Artikel ini membahas tentang persepsi karyawan terhadap dukungan organisasi. Studi ini menggunakan survei online di salah satu cabang bank syariah terkemuka di Indonesia. Data dianalisis menggunakan model persamaan struktural-partial least square (SEM-PLS). Hasil penelitian menunjukkan masalah dengan praktik manajemen sumber daya manusia (SDM), dukungan organisasi yang dirasakan, dan komitmen organisasi dari bank syariah, menghasilkan potensi turnover yang tinggi. Praktek HRM dan dukungan organisasi dirasakan secara positif dan signifikan berhubungan dengan komitmen organisasi. Namun, dukungan organisasi hanya memediasi hubungan antara praktik HRM dan komitmen normatif dan afektif, tetapi bukan hubungan antara praktik HRM dan komitmen berkelanjutan.